PEER FEEDBACK ON STUDENT TEACHERS’ TEACHING PRACTICE THROUGH MICROBLOGGING WITH INSTAGRAM - Lilia Indriani (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2022)
Technology integration in foreign language classroom is a prerequisite in this post pandemic era. Social media technologies have a great promise to boost efficacy of language learning and students’ engagement. As one of the social media platforms, Instagram rapidly gained popularity, with one billion registered users in 2018 and it is still growing bigger today.  It introduced hashtags to help users discover both photos and each other. As student teachers of English, teaching skill is a big must. In teaching practice, the learning engagement is reflected by giving peer feedback. Creative and innovative peer feedback can encourage the student teachers’ professional development as a teacher. Therefore, this study sheds light on the use of Instagram as the media for giving student teachers peer feedback after they have teaching practice in the form of microblog by using carousel photos and hashtag in Instagram. Thus, qualitative method is chosen to capture the objective of the study by questionnaire, documentation and semi-structured interview. The finding of this study is expected to provide new insight to develop engagement especially in giving feedback in the teaching practice for EFL student teachers in this hybrid learning.